The association between the level of physical activity with spinal posture and physical fitness parameters in early adolescence - Strukcinskiene, Birute; Raistenskis, Juozas; Stukas, Rimantas; Strukcinskaite, Vaiva; Buckus, Raimondas; Sidlauskiene, Aurelija (Vojnosanitetski pregled, 2021)
Abstract Background/Aim. A low level of physical activity and sedentary lifestyle affects the body posture in adolescents. The aim of this study was to assess the core relation between the level of physical activity and spinal posture as well as physical fitness parameters in 11–14 years old teenagers. Methods. The cross-sectional study included 532 children, aged from 11 to 14 years. The study was carried out at three Lithuanian schools in 2011–2013. The Youth Physical Activity Questionnaire (YPAQ) was used to assess physical activity. Spinal posture was assessed according to the Hoeger visual posture assessment method. Physical capacity was evaluated using a 6-min walking test (6 MWT) and by calculating maximum oxygen consumption (VO2max). Other physical fitness such as the general balance, flexibility, explosive leg power and abdominal muscle endurance were evaluated by applying the European Fitness Test (Eurofit). According to time spent doing moderate to vigorous intensity physical activities (MVPA), the sample was divided into 2 groups – a low activity level group and moderate to vigorous intensity physical activity level group. We compared the spinal posture evaluation results and physical fitness parameters between groups as well as correlations between the duration of MVPA, spinal posture evaluation results and physical fitness parameters. Results. The study showed that 22.2% of teenagers had a low physical activity level and 16% of teenagers had an incorrect posture. The teenagers of low physical activity group were less physically fit and had the poorer posture than teenagers in the MVPA group. During the 6MWT, the teenagers in the low physical activity group walked on average 63.2 m less (p = 0.002), and their VO2max was 0.8 mL/kg/min lower (p = 0.006) than that of teenagers in the MVPA group. The teenagers in the low physical activity group also did not perform as well in the explosive leg power and abdominal muscle endurance tests compared to teenagers in the MVPA group. Correlations between the duration of MVPA and spinal posture evaluation results as well as some physical fitness parameters were very weak. Conclusion. The teenagers of low physical activity were less physically capable and had poorer posture than the teenagers in the MVPA group.